Islamic School Financial Management Based on Qs. Al-Isra 26–27: The Perspective of Fakhr Al-Razi's Interpretation - Bunga Wardatul Jannah; Diningrum Citraningsih (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
Effective, efficient, and accountable financial management is a fundamental aspect in realizing quality education in Islamic schools, and this is in line with the message of QS. Al-Isra' verses 26–27. This study applies a qualitative approach through a literature study method, with the main sources being Tafsir Fakhr Ar-Razi and relevant scientific articles published in the last five years. The results of the study indicate that ideal education fund management can be achieved through the implementation of four management functions (POAC): directed planning, clear organization, targeted implementation, and transparent supervision. Specifically, the interpretation of Fakhr al-Din al-Razi emphasizes that the prohibition of tabdzir is not limited to material waste, but includes the use of assets that deviate from the right purpose and are not oriented towards the benefit, so that fund management requires both moral and rational responsibility. Although there are still various obstacles in its implementation, this finding confirms that the application of Qur'anic values can strengthen financial management practices so that they are more professional and support the improvement of the quality of education as a whole. Therefore, this research serves as an important reference for Islamic school managers in optimizing financial practices to be more structured, sustainable, and able to create an educational environment that is trustworthy, productive, inclusive, and oriented towards the success of students and the wider community.